Different muscle-recruitment strategies among elite breaststrokers - Guignard, B.; Olstad, B. H.; Simbaña Escobar, D.; Lauer, J.; Kjendlie, P.-L. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate electromyographical (EMG) profiles characterizing the lower-limb flexion-extension in an aquatic environment in high-level breaststrokers. Methods: The 2-dimensional breaststroke kick of 1 international- and 2 national-level female swimmers was analyzed during 2 maximal 25-m swims. The activities of biceps femoris, rectus femoris, gastrocnemius, and tibialis anterior were recorded. Results: The breaststroke kick was divided in 3 phases, according to the movements performed in the sagittal plane: push phase (PP) covering 27% of the total kick duration, glide phase (GP) 41%, and recovery phase (RP) 32%. Intrasubject reproducibility of the EMG and kinematics was observed from 1 stroke cycle to another. In addition, important intersubject kinematic reproducibility was noted, whereas muscle activities discriminated the subjects: The explosive PP was characterized by important muscle-activation peaks. During the recovery, muscles were likewise solicited for swimmers 1 (S1) and 2 (S2), while the lowest activities were observed during GP for S2 and swimmer 3 (S3), but not for S1, who maintained major muscle solicitations. Conclusions: The main muscle activities were observed during PP to perform powerful lower-limb extension. The most-skilled swimmer (S1) was the only 1 to solicit her muscles during GP to actively reach better streamlining. Important activation peaks during RP correspond to the limbs acting against water drag. Such differences in EMG strategies among an elite group highlight the importance of considering the muscle parameters used to effectively control the intensity of activation among the phases for a more efficient breaststroke kick.